Information required by the disabled travelers: a case study in Kukup Island, Tanjung Piai, Ledang Hills and Endau-Rompin Forest Park - Shalini Sanmargaraja; Seow, Ta Wee (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
Disabled tourism is being popular nowadays. However, the current tourism environment is not suitable for the use of disabled. Whether it is domestic or international travel, it involves travelers visiting the far destination from the original residential areas and using the services provided at the destination. Thus, the needs of travelers in terms of information and accessible facilities must be provided to attract tourists. However, incomplete source of information has been identified as a major weakness in disabled tourism. The objective of this paper is to review the information required by disabled travelers before they planned their holidays and to study the facility available in the national park at the study area. From the literature review, it is found that a wide range of information needed such as online accessibility, transportation, accommodation and disabled tourist attraction. Not all the national parks at the study area provided a website with complete information required by disabled travelers. From observation and audit method, it is found that the detailed facility planning should be done to improve the condition of the existing special facilities and building more facilities. Not all park managers are concerned and aware of the needs of disabled travelers. Business opportunities in the tourism sector can be created by addressing these barriers. Many disabled travelers will be planning for holidays if the information provided is complete and the accessibility of the tourism environment is created.